Dok-7 mutations underlie a neuromuscular junction synaptopathy. - Beeson, D; Higuchi, O; Palace, J; Cossins, J; Spearman, H; Maxwell, S; Newsom-Davis, J; Burke, G; Fawcett, P; Motomura, M; Müller, J; Lochmüller, H; et al. (2006)
Congenital myasthenic syndromes (CMSs) are a group of inherited disorders of neuromuscular transmission characterized by fatigable muscle weakness. One major subgroup of patients shows a characteristic "limb girdle" pattern of muscle weakness, in which the muscles have small, simplified neuromuscular junctions but normal acetylcholine receptor and acetylcholinesterase function. We showed that recessive inheritance of mutations in Dok-7, which result in a defective structure of the neuromuscular junction, is a cause of CMS with proximal muscle weakness.